2014
DOI: 10.1002/pd.4406
|View full text |Cite
|
Sign up to set email alerts
|

First trimester screening can predict adverse pregnancy outcomes

Abstract: Methods: We retrospectively reviewed and performed 4D-HDFI in 204 normal and 33 fetuses with confirmed diagnosis of cardiac anomalies of the great arteries. Cardiac volumes were available for post-analysis to obtain 4D rendered images of the great arteries. For the normal fetuses, two other traditional modalities including colour Doppler and HDFI were used to detect aortic arch and its branches and comparisons were made between each of these traditional methods and 4D-HDFI. Results: Two cases of interrupted ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 96 publications
(126 reference statements)
0
17
0
Order By: Relevance
“…Although many studies have attempted to find a predictive marker for SGA and IUGR, as recently reviewed by me and by Sharp and Alferivic, only a few studies have evaluated PV which, instead, should be considered as an early and independent marker of SGA with a better performance when compared with a placental biomarker, such as PAPP‐A and placental growth factor . In fact, circulating levels of biochemical markers secreted by placental tissue may only be a reflection of the volume of the placental tissue which, therefore, should be considered a better predictor of fetal and neonatal weight.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have attempted to find a predictive marker for SGA and IUGR, as recently reviewed by me and by Sharp and Alferivic, only a few studies have evaluated PV which, instead, should be considered as an early and independent marker of SGA with a better performance when compared with a placental biomarker, such as PAPP‐A and placental growth factor . In fact, circulating levels of biochemical markers secreted by placental tissue may only be a reflection of the volume of the placental tissue which, therefore, should be considered a better predictor of fetal and neonatal weight.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that performances reported in development studies may be confirmed in external validation studies, prediction models for GDM show a performance at least as good as traditional risk factor screening, as recommended by current guidelines [48,49]. However, prediction model-based GDM screening might offer the opportunity to reduce the burden of diagnosing GDM (e.g., only applying an OGTT to women at high risk of developing GDM).…”
Section: Discussionmentioning
confidence: 99%
“…Several promising biomarkers have been proposed to identify women at the risk of subsequently developing preeclampsia, foetal growth restriction and spontaneous preterm birth [52].…”
Section: First-trimester Diagnosis Of Major Obstetrical Disordersmentioning
confidence: 99%